2000
DOI: 10.1038/sj.ejcn.1600973
|View full text |Cite
|
Sign up to set email alerts
|

A combined heart rate and movement sensor: proof of concept and preliminary testing study

Abstract: Objective: Heart rate monitoring has previously been used as a technique for measuring energy expenditure (EE) in ®eld studies. However, the combination of heart rate monitoring with movement sensoring could have theoretical advantages compared to either method used alone. Therefore, this study was undertaken to develop and validate a new combined heart rate monitor and movement sensor instrument (HR M) for measuring EE. Methods: The HR M instrument is a single-piece instrument worn around the chest which reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…This sensor has recently been developed in order to allow measurement of human energy expenditure in a 'free-living' environment and has been validated against whole-body calorimetry using a fixed activity protocol. 22 It consists of a single-piece waterproof monitor attached to two standard ECG electrodes placed on the subjects' chest. For the current study, the sensor was set to measure movement and heart rate every 30 s over the 4-day-period.…”
Section: Oxyntomodulin and Energy Balance K Wynne Et Almentioning
confidence: 99%
“…This sensor has recently been developed in order to allow measurement of human energy expenditure in a 'free-living' environment and has been validated against whole-body calorimetry using a fixed activity protocol. 22 It consists of a single-piece waterproof monitor attached to two standard ECG electrodes placed on the subjects' chest. For the current study, the sensor was set to measure movement and heart rate every 30 s over the 4-day-period.…”
Section: Oxyntomodulin and Energy Balance K Wynne Et Almentioning
confidence: 99%
“…Thus, it remains a continuing goal to develop and evaluate methods for measuring PAEE and its subcomponents that are also affordable and minimally invasive. Methods which integrate physiological and motion detection systems have been identified as a promising research area (LaMonte & Ainsworth, 2001) and previous studies have demonstrated the utility of combined HR and movement measurement to improve precision of PAEE and PAI (Avons et al, 1988;Haskell et al, 1993;Moon & Butte, 1996;Luke et al, 1997;Treuth et al, 1998;Rennie et al, 2000;Strath et al, 2001;Strath et al, 2002;Brage et al, 2003b, c;2004). However, no single commercially available device integrating HR and movement sensing has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a sigmoid function with smoothed heart rate could improve the estimate of total energy expenditure in studies using simultaneous measurement of heart rate and motion sensing to study both total energy expenditure and patterns of activity in free-living subjects (Rennie et al, 2000;Strath et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In 13 C-breath tests, it is important to have an accurate estimate of VCO 2 at both resting and nonresting levels of energy expenditure. An improved calibration method would also be useful for studies of total energy expenditure and patterns of activity that utilize simultaneous measurement of heart rate and motion sensing (Rennie et al, 2000;Strath et al, 2002).…”
Section: Introductionmentioning
confidence: 99%